2016
DOI: 10.4081/itjm.2016.798
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of carbapenem-resistant Klebsiella pneumoniae infections

Abstract: In the nosocomial setting, antimicrobial-resistant Enterobacteriaceae are a growing challenge, and alarming trends in resistance are currently reported all over the world. Isolates of Enterobacteriaceae producing ampC β-lactamases and extended spectrum β-lactamases are endemic in many hospitals, and are frequently resistant also to other classes of antibiotics, such as fluoroquinolones and aminoglycosides. The risk of infections due to multi-drug resistant strains should be considered also for outpatients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Third-generation cephalosporins have been the treatment of choice for Gram-negative bacteria, including K. pneumoniae, but nowadays, they are largely ineffective due to the emergence of ESBL-producing bacteria [ 8 ]. This was also true in our study, in which one of the high antimicrobial resistance was against 3rd and 4th generation cephalosporins, ceftriaxone (97%), cefotaxime (97%), cefepime (84.1%), and ceftazidime (65.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third-generation cephalosporins have been the treatment of choice for Gram-negative bacteria, including K. pneumoniae, but nowadays, they are largely ineffective due to the emergence of ESBL-producing bacteria [ 8 ]. This was also true in our study, in which one of the high antimicrobial resistance was against 3rd and 4th generation cephalosporins, ceftriaxone (97%), cefotaxime (97%), cefepime (84.1%), and ceftazidime (65.9%).…”
Section: Discussionmentioning
confidence: 99%
“…It has gained attention worldwide, especially in developed countries, due to its high drug resistance. Antimicrobial resistance rates in K. pneumoniae have steadily increased over the years, and K. pneumoniae is becoming resistant to virtually all aminoglycosides, quinolones, and β-lactams [ 8 ]. For instance, at the European level, more than one-third (36.6%) of K. pneumoniae isolates reported to the European antimicrobial resistance surveillance network for 2019 were resistant to at least one of the antimicrobial groups under regular surveillance, i.e., fluoroquinolones, third-generation cephalosporins, aminoglycosides, and carbapenems [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of multidrug-resistant bacteria is one of the main concerns for critically ill patients [ 21 ], and selecting an appropriate antibiotic regimen is essential to preventing the onset of multidrug-resistant infections [ 22 ]. In this study, we found that previous exposure to aminoglycosides, linezolid, penicillins, and colistin increases the likelihood of developing an infection sustained by MDR-Kp among ICU patients, contributing to strengthening the existing literature in this field, which is often inconsistent [ 15 ].…”
Section: Discussionmentioning
confidence: 99%